2016
DOI: 10.1080/14017431.2016.1262546
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of cardiovascular outcomes in patients treated with ASV

Abstract: In CHF patients with CSR, 18 months ASV treatment did not significantly affect cardiovascular death or combined cardiovascular death or hospital admissions. But there was a trend toward better combined outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Nonrandomized controlled trials did not confirm the findings of an adverse effect of ASV on cardiovascular mortality. 26,27 Although meta-regression has shown that treating CSA/CSR with PPV seems to be more effective in improving LVEF when systolic function is more impaired, the mortality risk was markedly increased in the subgroup of patients with HFrEF in the SERVE-HF trial allocated to ASV with an LVEF < 30%. 28 Taken together, this supports that the adverse outcome observed in the ASV arm of the SERFE-HF trial is likely due to arrhythmia and not the effects on cardiac function.…”
Section: Results In the Context Of The Literaturementioning
confidence: 99%
“…Nonrandomized controlled trials did not confirm the findings of an adverse effect of ASV on cardiovascular mortality. 26,27 Although meta-regression has shown that treating CSA/CSR with PPV seems to be more effective in improving LVEF when systolic function is more impaired, the mortality risk was markedly increased in the subgroup of patients with HFrEF in the SERVE-HF trial allocated to ASV with an LVEF < 30%. 28 Taken together, this supports that the adverse outcome observed in the ASV arm of the SERFE-HF trial is likely due to arrhythmia and not the effects on cardiac function.…”
Section: Results In the Context Of The Literaturementioning
confidence: 99%
“…In central sleep apnea syndrome specific is the cessation of breathing during sleep due to the total abolishment of respiratory muscle activity, by the absence of nerve impulse . This syndrome can be divided (2,3) into several categories, each with a unique physiopathology and a specific treatment.…”
mentioning
confidence: 99%
“…(9) Despite progress over the last 3 decades, HF continues to have high morbidity and mortality rates . At this time, it is uncertain (1,3) whether CSAS is a consequence of HF with reduced ejection fraction or it is in fact a risk factor for the evolution of underlying cardiac pathology.…”
mentioning
confidence: 99%